Formulating outputs from a mixed-methods study of access to general practice: a series of collaborative stakeholder workshops - Helen Atherton; Toto Gronlund; Abi Eccles; Carol Bryce; Angela Martin; Catherine Pope (Health and Social Care Delivery Research)
Background Access to general practice is a concern for policy-makers, politicians, service providers and the public. We conducted a study to examine what happens in the long term to general practices that have introduced innovations designed to improve access to appointments. Recognising the importance of ensuring research findings are transferable to those using them, we used collaborative workshops to aid the development of our study outputs. Methods We held three sequential interactive workshops. These covered (1) early findings of the study, (2) what evidence-based resources attendees use and (3) what resources they would like to see produced. We sought to include 6–12 people from staff from practices participating in the wider research study, from primary care networks, from partnership boards of integrated care systems, clinical commissioners, professional bodies, National Health Service bodies and independent think tanks. The first two workshops were online, the final was in-person. Workshops were facilitated by the research team, including the patient and public involvement lead. A research team member took detailed notes. Results Workshop 1 had 12 attendees; workshop 2 had 9 attendees, of which 7 were also at the previous workshop; workshop 3 had 7 attendees, of whom 6 had attended a previous workshop. From these workshops, we gained insights that helped us to validate our interpretation of the study data. We observed the competing interests and needs of different groups, who have different perspectives on the value of research evidence. Outputs that are brief, written in lay terms and widely publicised appear to be of especial value. Limitations The range of stakeholders included was less varied than intended; this was in part due to the commitment involved in attending, and this may limit the inclusivity of the findings. Future work This approach could be used in future studies to ensure that stakeholder interests are included in study dissemination plans. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR133620. Plain language summary The GPSUS study looks at the access to general practice and how approaches to offering appointments can be better and long-lasting, when demand is high, and the National Health Service is under lots of pressure. We wanted to ensure that the findings from our study reached the right people in the best way, and to do this, we held collaborative workshops with people from policy and academic backgrounds, and those working in general practice. We held three workshops, one in February 2024, one in March 2024 and one in April 2024. We invited staff from the general practices taking part in the study, academics with expertise in this area, policy-makers at national and local level, and representatives from professional bodies and thinktanks. Of 21 people invited, 1 declined and 6 did not respond. The remaining 14 were able to attend one or more of the workshops. Workshop 1 had 12 attendees; workshop 2 had 9 attendees, of which 7 were also at the previous workshop; workshop 3 had 7 attendees, of whom 6 had attended a previous workshop. During workshop 1, we described the study and shared early findings. Attendees shared their perspectives on the findings. During workshop 2, we discussed what kind of resources are useful and how these can be shared. During workshop 3, we shared example outputs and discussed the advantages and disadvantages of these. From the learning in these workshops, we planned for the outputs we will produce before the end of the GPSUS study.